2015
DOI: 10.1097/nnd.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Workshop to Support Evidence-Based Practice Change in Long-Term Care

Abstract: To support evidence-based practice changes in long-term care, we used a practice development approach with interactive workshops to engage teams from 10 organizations in participatory change. Data from postworkshop surveys and subsequent semistructured interviews indicated that participants felt empowered to identify a priority challenge and initiate change. Notably, the workshop intervention enhanced collaboration between professional and unregulated staff, fostered the development of shared vision, and provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Higuchi et al have shown that interactive and collaborative workshop activities enable people to successfully choose a shared focus for change and identify feasible steps to start the evidence‐based change process. Moreover, sharing success stories is an effective way to help build self‐efficacy and initiate change because reflecting on successful strategies allows people to create an attitude of empowerment which is a requirement for sustainable evidence‐based change (Higuchi et al, 2015). Employing a combination of dynamic teaching/learning techniques that involve learners in their learning process is an effective strategy for knowledge transfer and evidence‐based changes (Patelarou et al, 2017; Turenne et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higuchi et al have shown that interactive and collaborative workshop activities enable people to successfully choose a shared focus for change and identify feasible steps to start the evidence‐based change process. Moreover, sharing success stories is an effective way to help build self‐efficacy and initiate change because reflecting on successful strategies allows people to create an attitude of empowerment which is a requirement for sustainable evidence‐based change (Higuchi et al, 2015). Employing a combination of dynamic teaching/learning techniques that involve learners in their learning process is an effective strategy for knowledge transfer and evidence‐based changes (Patelarou et al, 2017; Turenne et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Higuchi et al have shown that interactive and collaborative workshop activities enable people to successfully choose a shared focus for change and identify feasible steps to start the evidence-based change process. Moreover, sharing success stories is an effective way to help build self-efficacy and initiate change because reflecting on successful strategies allows people to create an attitude of empowerment which is a requirement for sustainable evidence-based change (Higuchi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There were three intervention elements: on‐site workshop, toolkit for action plan implementation, and complementary support by a facilitator and regional Best Practice Coordinators (BPCs). During the initial 1‐day workshop, participants related previous success stories in their organization, described practice challenges, identified the focus of and built a case for a practice change, and developed implementation steps for an action plan (Higuchi, Edwards, Carr, Marck, & Abdullah, ). Workshops were interactive and tailored to individual sites.…”
Section: Methodsmentioning
confidence: 99%
“…The most successful changes within LTC promote teamwork and highlight the resident benefits of the initiative. ( 30 , 31 ) Interactive workshops/meetings that provide interdisciplinary connection strengthen personal staff relationships and unity; ( 30 , 32 ) follow-up meetings that clarify and refresh the change process as it unfolds are sustaining. ( 30 , 31 ) Strategic reminders are effective in promotion, ( 31 ) as is the identification of a change champion, a peer with new protocol expertise who takes responsibility for implementation.…”
Section: Resultsmentioning
confidence: 99%